INFLUENCE OF MOTIVATION, PERCEIVED WORK ENVIRONMENT AND WORK DISCIPLINE OF INTENTION TO TURNOVER EMPLOYEES (STUDY IN CV.SANITAS BAKERY) - Nawang Wulan Setyawan, 12.05.51.0042 (Students Journal of Economic and Management, 2016)
This study analyzed the effect of Work Motivation, Work Environment and Work Discipline Against Perceived Intention to Turnover Employess.Objek to research in this paper on CV.SANITAS BAKERY Semarang.Teknik sampling using census study, which is sampling all employees became respondents, totaling 100 respondents with data collection method using a questionnaire (questionnaire) by distributing questionnaires to the respondents in order to obtain research informasi.Tujuan formulated to determine the effect Motivation,Perceived Work Environment, Work Discipline of the Intention to Turnover Employees. The data collected is tested the validity of the method of product moment and tested for validity by the coefficient alpha (alpha cronbrach), where the results of all the data is valid and reliable, to test the reliability, each of the independent variables were tested with multiple regression analysis, t test, and the test F.Hasil of analysis and discussion show that: (1) Work Motivation and significant negative effect on Employee Turnover Intention to higher motivation, the desire of employees out / move less and less; (2) Working Environment Perceived and significant negative effect Intention to Turnover higher employee work environment influences, terpersepsi the desire of employees to get out / move less and less; (3) work discipline and significant negative effect Intention to higher employee turnover rate influence labor discipline, the desire of employees to get out / move less and less.Â Keywords: Motivation,Perceived Work Environment, Work Discipline, Intention to Turnover Â